Management of suspected and confirmed recurrent venous thrombosis while on anticoagulant therapy. What next?. Issue 180 (August 2019) - Rodger, Marc A.; Miranda, Sebastien; Delluc, Aurelien; Carrier, Marc
Abstract: Suspected recurrent venous thromboembolism (VTE) is a common and vexing clinical problem. Confounding the diagnosis of recurrent VTE is a high frequency of residual VTE from prior VTE. The diagnosis of recurrent VTE must be established by comparing current imaging with past imaging to distinguish acute from chronic thrombosis. Next, we must ascertain if non-compliance was the cause of "apparent therapeutic failure" and if non-compliance is at play then re-initiate anticoagulant therapy. Therapeutic failure is relatively uncommon. As such, we must consider underlying causes of therapeutic failures including malignancy and potent thrombophilias. Finally, short term anticoagulant management of therapeutic failures is controversial, and requires further research, but the best current evidence supports a course of full-dose low-molecular-weight heparin (LMWH) (and dose escalated LMWH if failure occurs while on full-dose LMWH). Highlights: Suspected recurrent venous thrombosis is common First objectively confirm the recurrence then consider the etiology of recurrent VTE and decide whether to change/escalate anticoagulant therapy Non-compliance is a concern in recurrent VTE